The Role of ASEAN and Korean Youth for Future-Oriented Partnership: Sustainable Innovation on Making “Food Waste Bite-Size Snacks” - Salsa Febiola Gading Widjaya; Afissa Hanani Oktavia; Muhammad Indrawan Jatmika (Future Science, 2022)
Food waste is often considered garbage without further processing. This way of thinking eventually leads to waste in the form of food waste that accumulates. The existence of this issue requires contributions from various parties, including state or non-state actors, including the role of youth as future state leaders. Through gastro-diplomacy, the participation of state and non-state actors in overcoming this issue will result in significant solutions. One solution that could be done by the contribution of the state and youth is to reuse leftover food into food or snacks that have a high-selling value. If this initiative can be carried out massively in ASEAN countries and Korea, the accumulation of waste or the percentage of food waste will drastically decrease. In addition, food from leftovers can be traded and will improve people's living standards. Food from leftovers can be used as a diplomatic tool between ASEAN countries and Korea in overcoming the issue of food waste. In this paper, it will be ex- plained further regarding how the role or contribution of the state and youth community can go hand in hand and can achieve the same goal, namely reducing food waste and turning it into ready to sell snacks.